BARRIERS TO TECHNOLOGY INTEGRATION FOR TEACHERS IN THAI-CURRICULUM SCHOOLS - Veerathanongdech, Wachirawut Bobby (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
Education reform with technology use has been in the works since the 1997 Constitution of Thailand, but Thai student achievement has not improved overall. This research investigates any influence of Technology Integration barriers that are external and internal to the teacher, on their intention to integrate technology in the classroom. 105 teachers of Thai-curriculum schools were sampled, and their data was collected by Technology Integration Barrier Survey (TIBS). Multiple Linear Regression was used to find relationships between external and internal barriers to teachers’ behavioral intention to integrate technology in the classroom, respectively. The result was teachers did not face strong external or internal barriers, with only a temperate level of intention to integrate technology in the classroom. Internal barriers were found to influence teachers’ intention to integrate technology. This research recommends continued but heightened teacher support and technological leadership training to maintain and bolster technology integration above present levels, and further research to explore other influences on student achievement.